Potential Opportunities and Challenges for Research Collaboration with Latin America in Agriculture and Food Science - Esquivel Rodríguez, Patricia (2017)
Latin America (LatAm) is an ethnic and geographic concept associated with those areas of the American continent where romance languages (Spanish, Portuguese, or French) predominate, i.e., Mexico, Central and South America, and most of the Caribbean islands. According to data of the World Bank,(1) the total population of the region is approximately 640 million people and most countries have underdeveloped or developing economies. Brazil, Argentina, Chile, Colombia, and Peru have highest the Gross Domestic Product (GDP, in 2017) of the group.